Species richness, productivity and quality assessment of grassland resources in hill agroecosystem of western Himalaya - DEV, INDER; RADOTRA, SUDESH; RAM, ASHA; SINGH, J P; DEB, D; ROY, M M; SRIVASTAVA, M; KUMAR, PARDEEP; AHMAD, SUHEEL; CHAURASIA, R S (The Indian Journal of Animal Sciences, 2018)
Livestock contribution in agricultural economy is significantly higher in hilly regions of India. A detailed study was carried out to assess the productivity, species richness and diversity of grasses of the grasslands in different hill agro-ecosystems of Kangra district of Himachal Pradesh in western Himalaya. Saccharum spontaneum (low hills), Chrysopogon echinulatus (mid hills) and Festuca spp. (high hills) were observed as the most dominant species in hill agro-ecosystems. Productivity assessment was done at five locations, viz. open forest area; enclosed forest area; community land; farmers’ field; and wasteland in each hill zone. High species richness and diversity was observed in mid hill zone as compared to low and high hills. The mean production level was recorded highest in low hills closely followed by mid hills; much less in high hills. Amongst the land-use systems, highest biomass production was recorded at farmers’ field followed by community land and least in wasteland situation. The average herbage production obtained through six cuts at periodic intervals (March to December) was 3,202 DM kg/ha, while in single harvest it was 2,249 DM kg/ha (low-hill conditions); 2,893 and 1,924 DM kg/ha (mid-hill conditions) and 1,399 and 850 DM kg/ha (high-hill conditions), respectively. Averaged over the different locations, 6.01, 6.64 and 10.87% crude protein (CP) was observed (in multicut situation) in low, mid and high hills respectively. Average herbage production obtained through six cuts at periodical intervals (March-December) was consistently higher as compared to single harvest in all the three zones.